Frozen core-annular flow model for effervescent atomizer - Amaro, Jordan [UNESP]; Mendiburu, Andres Z.; Santos, Leila Ribeiro dos; Carvalho Jr, Joao A. de [UNESP] (Springer, 2022)
This research consists in the development of a frozen core-annular flow model to estimate the physical variables of the fluids at the exit orifice of the effervescent atomizer. The model is validated through experimental results of the mean thickness of the ligaments, obtaining excellent estimates for GLR >= 1.0%. The model is used to simulate five operating conditions in 17 effervescent atomizers. The results obtained show that the geometric variables defining the atomizer design have no significant influence on the estimated physical variables. The estimated physical variables are: (a) gas volume fraction, (b) dimensionless two-phase pressure, (c) dimensionless gas temperature, (d) dimensionless two-phase density, (e) liquid velocity, (f) gas velocity, and (g) liquid thickness. The ranges for the velocity and thickness of the liquid are [7.976, 26.892 m/s] and [165, 641 mu m], respectively. Finally, a dimensionless model is established to estimate the integral Sauter mean diameter (ID32) of the spray droplets. The dimensionless model is characterized by having R-2 = 0.734 and RMSE = 3.165, so it is considered good for making future predictions.
Keywords: Effervescent atomization; Spray; Model